Routine reporting of grey-white matter differentiation in early brain computed tomography in comatose patients after cardiac arrest: A substudy of the COACT trial. (June 2022) - Adriaansens, K.O.; Jewbali, L.S.D.; Lemkes, J.S.; Spoormans, E.M.; Meuwissen, M.; Blans, M.J.; van der Harst, P.; Eikemans, B.J.W.; Bleeker, G.B.; Beishuizen, A.; Henriques, J.P.; van der Lugt, A.; et al.
Abstract: Aim: A multimodal approach is advised for neurological prognostication in comatose patients after out-of-hospital cardiac arrest (OHCA). Grey-white matter differentiation (grey-white ratio, GWR) obtained from a brain CT scan performed < 24 hours after return of circulation can be part of this approach. The aims of this study were to investigate the frequency and method of reporting the GWR in brain CT scan reports and their association with outcome. Methods: This is a post-hoc descriptive analysis of the COACT trial. The primary endpoint was the reporting of GWR by the radiologist. Secondary endpoints were APACHE IV score, Cerebral Performance Categories at discharge and 90-day follow-up, Glasgow Coma Scale at discharge, GWR-stratified 1-year survival, and RAND-36 stratified by normal versus abnormal GWR. Associations were analysed using multivariable analysis. Results: A total of 427 OHCA patients were included in this study, 234 (55%) of whom underwent a brain CT scan within 24 hours after ROSC. Median time between arrest and initial CT scan was 12 hours. In 195 patients (83%), the GWR was described in the reports, but always expressed qualitatively. The GWR was deemed abnormal in 57 (29%) CT scans. No differences were found in secondary endpoints between the two groups. Conclusion: GWR was frequently described in CT scan reports. Early abnormal GWR, as assessed qualitatively by a radiologist within 24 hours after ROSC, was a poor predictor of neurological prognosis.